Comparative study using small-angle x-ray scattering and nitrogen adsorption in the characterization of silica xerogels and aerogels - Vollet, D. R. [UNESP]; Donatti, D. A. [UNESP]; Ibañez Ruiz, A. [UNESP] (American Physical Society (APS), 2004)
A comparative study using small-angle x-ray scattering (SAXS) and nitrogen adsorption has been carried out in the structural characterization of silica xerogels and aerogels, obtained from tetraethoxysilane sonohydrolysis. The specific surface and the mean pore size as measured by both the techniques were found to be in notable agreement in all cases for aerogels and xerogels. According to the SAXS data, aerogels at 500 °C exhibit a mass fractal structure with fractal dimension D∼2.4 in the range between the correlation length ξ∼5.3 nm and a∼0.75 nm. An experimental method to probe the mass fractal structure of aerogels from exclusively nitrogen adsorption isotherms has been presented. For aerogels at 500 °C, we have found D∼2.4 in the range between the pore width 2rξ∼33 nm and 2ra∼4.5 nm, which is in notable agreement with the SAXS results (D ∼2.4, ξ∼5.3 nm, a∼0.75 nm) if we assign the pore width 2r probed by the Kelvin equation in the adsorption method to the Bragg distance 2π/q associated to the correlation length 1/q probed by SAXS.
Keywords: adsorption; analytic method; catalysis; ceramics; comparative study; evaporation; fractal analysis; gel; hydrolysis; nitrogen deposition; radiation scattering; sampling; technique